Implementation of Management Based on Islamic Spiritual Entrepreneurship for the Success of Madrasah Management - Muhammad Sadri; Faisar Ananda; Saparuddin Siregar (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2020)
This study discusses how the implementation of Islamic Spiritual Entrepreneurship-based madrasa management in achieving the success of madrasa management in Langkat. The form of madrasa management based on Islamic Spiritual Entrepreneurship management which is analyzed through the form of the process of implementing education, funding, marketing / promotion, human resource management and the environment which is carried out based on the concept of Islamic Spiritual Entrepreneurship (honesty, gratitude, Islamic values, blessings of Allah SWT and the concept of worship. to Allah SWT). The location of this research was conducted at 60 madrasa in Langkat by taking sambel 300 respondents consisting of leaders, teachers, education staff and management. The research is field research using naturalistic qualitative techniques. The data were collected using interview, observation and documentation methods. The data were analyzed and verified and then concluded that it was inductive. The results of the study prove that 1) madrasas in Langkat have not maximally implemented Islamic Spiritual Entrepreneurship on school management because there is no strong commitment to all management to apply the concept 2) Not all Islamic Spiritual Entrepreneurship management criteria are applied in the management of madrasa which are religious-based schools of Islam 3) Collaboration is needed from TOP Management to students in applying the concept of Islamic Spiritual Entrepreneurship in school management so as to achieve competitive advantage and management sustainability until the future.